Imaging of prostate cancer: optimizing affinity to prostate specific membrane antigen by spacer modifications in a tumor spheroid model. Issue 20 (29th November 2022) - Krishnan, Mena Asha; Pandit, Amit; Sharma, Rajesh; Chelvam, Venkatesh
Abstract: Early diagnosis of prostate cancer (PCa) is crucial for staging, treatment and management of patients. Prostate specific membrane antigen (PSMA), highly over-expressed on PCa cells, is an excellent target for selective imaging of PCa. In recent years, various scaffolds have been explored as potential carriers to target diagnostic and therapeutic agents to PSMA + tumour cells. Numerous fluorescent or radioisotope probes linked via a peptide linker have been developed that selectively binds to PCa cells. However, there are very few reports that examine the effects of chemical modifications in the peptide linker of an imaging probe on its affinity to PSMA protein. This report systematically investigates the impact of hydrophobic aromatic moieties in the peptide linker on PSMA affinity and in vitro performance. For this, a series of fluorescent bioconjugates 12 –17 with different aromatic spacers were designed, synthesized, and their interactions within the PSMA pocket were first analysed in silico . Cell uptake studies were then performed for 12 –17 in PSMA + cell lines and 3D tumour models in vitro . Binding affinity values of 12 –17 were found to be in the range of 36 to 157.9 nM, and 12 with three aromatic groups in the spacer exhibit highest affinity (KD = 36 nM) compared to 17 which is devoid of aromatic groups. These studies suggest that aromatic groups in the spacer region can significantly affect deep tissue imaging of fluorescent bioconjugates. Bioconjugate 12 can be a promising diagnostic tool, and conjugation to near-infrared agents would further its applications in deep-tissue imaging and surgery. Communicated by Ramaswamy H. Sarma